2019
DOI: 10.2478/acph-2019-0052
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of olive oil polyphenols and their combinations with anticancer drugs

Abstract: Cancer presents one of the leading causes of death in the world. Current treatment includes the administration of one or more anticancer drugs, commonly known as chemotherapy. The biggest issue concerning the chemotherapeutics is their toxicity on normal cells and persisting side effects. One approach to the issue is chemoprevention and the other one is the discovery of more effective drugs or drug combinations, including combinations with polyphenols. Olive oil polyphenols (OOPs), especially hydroxytyrosol (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 112 publications
1
40
0
Order By: Relevance
“…Besides, the easy modification of the allows their association with other antitumor drugs and molecules that can target specifics cells, such as cancer cells 89 . Researchers have been reported the beneficial effects of the combination between anticancer agents and polyphenols 90 , 91 , as well as compounds found in BRP 92 94 . Qiao et al 95 showed that green tea catechins associated with antitumor drugs are more effective than monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the easy modification of the allows their association with other antitumor drugs and molecules that can target specifics cells, such as cancer cells 89 . Researchers have been reported the beneficial effects of the combination between anticancer agents and polyphenols 90 , 91 , as well as compounds found in BRP 92 94 . Qiao et al 95 showed that green tea catechins associated with antitumor drugs are more effective than monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…of the 80% alcoholic extract of olive leaves, containing oleuropein, HT, caffeic acid, tyrosol, apigenin, and verbascoside [26,27]. Biophenols can also be used to develop new drugs useful to combat chronic inflammatory conditions, the risk of thrombosis, CVD-related states such as atherosclerosis [28], cancer [29], also in combination with anti-cancer drugs [30], as well as to reduce amyloid deposition associated with T2DM and aging-related states such as neurodegeneration [1,31] ( Figure 1). Finally, the molecular scaffolds of plant polyphenols are also investigated to develop new molecules potentially exploitable in disease prevention and therapy [32].…”
Section: Polyphenols: Important Players Of the Mediterranean/asian Dietsmentioning
confidence: 99%
“…In human colon cancer DLD1 cells, hydroxytyrosol induced cell apoptosis, and the activation of PIPK3/AKT pathway through ROS production [44]. Accordingly, incubation with the only extract obtained from OWW, at the highest concentration, significantly increased the generation of ROS, which might be useful to activate specific intracellular signals leading to cell death as already shown by others [44,45]. Furthermore, we found that at the highest concentration level, incubation with the extract obtained from OP reduced cell viability.…”
Section: Discussionmentioning
confidence: 71%